Spinal Tuberculosis: Age Distribution of the Patients (Faridpur Medical College Journal, 2016)
This cross sectional epidemiological study was done in National Centre for Tuberculosis and Research and 250 bed TB Hospital, Shyamoli Dhaka. In this study 107 patients of diagnosed spinal tuberculosis attending the hospital during January 2007 to December 2014 were included. The purpose of this study was to analyze the age distribution of the patients with additional information on sex distribution and economic status. The study revealed that 19.6% of the patients were below the age of 15 years, of which 42.9% were within the age range of 11-15 years. Among the paediatric patients there was slight predominance of male sex (52.4%), while of the total patients female sex dominated (57%). Children of low income family, earning less than 10,000 taka per month, suffered the most (80.9%).Faridpur Med. Coll. J. Jan 2015;10(1): 14-16